Framing Analysis of Reporting on the Sinovac Covid-19 Vaccine Type on Kompas.Com Online Media - Eka Lestari; Tessa Shasrini (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
This article aims to find out how the news framing process is about the Sinovac Covid-19 vaccine in online media Kompas.com. This study used a qualitative analysis method using the Robert N. Etman framing analysis model. The subject of this research is the online media kompas.com, while the research object is news about the Sinovac Covid-19 vaccine. The news analyzed totaled 5 news published in 2021. The results of the define problem research show that the online media kompas.com constructed the covid 19 type sinovac vaccine which is very feasible and good for consumption by the public ranging from children to pregnant women, this has conducted clinical trials as a diagnosis of causes. Kompas.com online media explores the make moral judgment that this vaccine has protected the public and educational staff from the virus, so the framing contains a treatment recommendation that the vaccine is appropriate for dissemination and campaigning to the public.